Tennessee teacher licensure agency - Kinkead, Gwen, 1951-; Kaplan, Edward H., 1936- (London : Yale School of Management, 2022)
Haliday Douglas was taken aback when a headhunter called him about a position for which he appeared to lack any training or experience. Douglas was informed by the interviewers that the licensure agency served as a holding facility for individuals until they retired. The Tennessee state educator licensing office was given to Haliday Douglas to run. The task at hand was to reform the state's educator licensing system. "It was a hot mess and I'm attracted to hot messes," Douglas says of his new job. He signed on, delighted.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Management -- Case studies; Organizational change -- Case studies; Teachers -- Certification -- Tennessee -- Case studies